Ocean and Marine Stewardship in Africa: The Marine Stewardship Council Certification in Namibia and The Gambia - Nyiawung, Richard Achankeng; Erasmus, Victoria Ndinelago (Frontiers in Marine Science, 2022)
Ocean and marine stewardship activities across different geographical areas contribute to global sustainability efforts, management, and conservation of ocean resources. The Marine Stewardship Council (MSC), through its sustainability standards and market-based mechanisms, rewards best practices for wild-caught seafood. To date, very few fisheries in Africa have participated in the MSC program and obtain its certification. This paper explores the MSC certification in the African continent by examining two case studies: the Namibian hake (Merluccius capensis and M. paradoxus) trawl and longline fishery and The Gambian sole fishery (Cynoglossus senegalenis and Synaptura cadenati). Drawing on document analysis, institutional ethnography, and extensive collaborative research with actors in these fisheries, we utilize three stewardship dimensions, i.e., Care-Knowledge-Agency, to qualitatively analyze how the MSC program provides an opportunity of actors to design ocean stewardship tools and promote fisheries sustainability in Africa. The Namibian fishery demonstrates a large-scale fishery with the adequate agency, technical knowledge, and interest in self-design improvements and stewardship, compared to the Gambian fishery, a small-scale fishery motivated to achieve certification but depends largely on external support to coordinate improvements and stewardship activities. The key motivation for Namibia and The Gambia actors to participate in the MSC certification is the interest in increasing their international market access while ensuring ecosystem-based management and sustainability of the fisheries. Successful engagement with MSC requires establishing good governance structures, involvement of local actors, technical knowledge, and sufficient financial resources. The paper demonstrates the need for practitioners, government/market-actors, and academia to encourage sustainable seafood management in Africa by promoting various national and regional sustainability campaigns, environmental awareness programs and ocean stewardship initiatives.